Plan de negocio Eco-Hotel Olas del Mar (2022)
Colombia is characterized for being a country where the tourist demand is quite significant, due to its natural wealth and the cultural variety that it possesses. Despite wanting to carry out business ideas in the tourism sector, it is usually a bit complex in terms of the variety of factors that must be taken into account for the realization and implementation, because it is a very important sector and that is in constant development. Through this project we will focus on empowering and making known the culture of the Colombian Caribbean region, proposing a comprehensive approach through the development of cultural activities that stand out in the Caribbean region, precisely in Santa Marta - Magdalena, which It provides a large amount of economic income and in this way enhances the cultural and natural wealth and the joy that characterizes the inhabitants of the Caribbean region.